Situation Report: Romania, 26 May 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Gromyko's Official Visit to Romania / by Vladimir Socor A Soviet History of Romania / by Dan Ionescu Government Reshuffle / by Paul Gafton Romania's Multimillion-Dollar Australian Ore Contract Fails to Materialize / by Mihai Sturdza Ceausescu's Latest Asia Tour / by Mihai Sturdza Aesthetics and Politics / by Crisula Stefanescu Humor and Politics / by Crisula Stefanescu